2007
DOI: 10.1074/jbc.m702824200
|View full text |Cite
|
Sign up to set email alerts
|

p62/SQSTM1 Binds Directly to Atg8/LC3 to Facilitate Degradation of Ubiquitinated Protein Aggregates by Autophagy

Abstract: Protein degradation by basal constitutive autophagy is important to avoid accumulation of polyubiquitinated protein aggregates and development of neurodegenerative diseases. The polyubiquitin-binding protein p62/SQSTM1 is degraded by autophagy. It is found in cellular inclusion bodies together with polyubiquitinated proteins and in cytosolic protein aggregates that accumulate in various chronic, toxic, and degenerative diseases. Here we show for the first time a direct interaction between p62 and the autophagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

84
3,159
2
30

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,933 publications
(3,341 citation statements)
references
References 55 publications
(35 reference statements)
84
3,159
2
30
Order By: Relevance
“…These results indicate that melatonin up‐regulates Parkin‐mediated mitophagy, thus eliminating dysfunctional mitochondrial and maintaining the homoeostasis of mitochondria in the diabetic heart. The linkage of the ubiquitin‐binding protein p62 to ubiquitin on the mitochondrion and lipidated LC3II on the autophagosome provides a physical attachment point for mitophagy 13, 22, 59. The present study also indicates that mitochondrial p62 increases after melatonin administration.…”
Section: Discussionsupporting
confidence: 65%
“…These results indicate that melatonin up‐regulates Parkin‐mediated mitophagy, thus eliminating dysfunctional mitochondrial and maintaining the homoeostasis of mitochondria in the diabetic heart. The linkage of the ubiquitin‐binding protein p62 to ubiquitin on the mitochondrion and lipidated LC3II on the autophagosome provides a physical attachment point for mitophagy 13, 22, 59. The present study also indicates that mitochondrial p62 increases after melatonin administration.…”
Section: Discussionsupporting
confidence: 65%
“…17,26 Additional acidic residues and/or serine/threonine phosphorylation sites preceding the hydrophobic LIR core sequence are also commonly found in LIR-containing proteins, and are demonstrated to regulate their specific interactions with Atg8-family members. 20,[30][31][32] Recently, a noncanonical LIR motif, which solely comprises 3 consecutive hydrophobic residues (LVV), has been found in the autophagy receptor CALCOCO2/NDP52. 33 This atypical LIR motif (termed as CLIR) exclusively interacts with the Atg8-family member, LC3C, and endows CALCOCO2 with a unique function in xenophagy.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence showed that the specific interactions between Atg8-binding proteins and Atg8-family proteins were mainly mediated by a short motif named LC3-interacting region (LIR). [20][21][22][23][24][25][26][27][28][29] The canonical LIR motif has the consensus core sequence QxxG where Q being aromatic residues (W/F/Y), and G being bulk hydrophobic residues (L/I/ V). 17,26 Additional acidic residues and/or serine/threonine phosphorylation sites preceding the hydrophobic LIR core sequence are also commonly found in LIR-containing proteins, and are demonstrated to regulate their specific interactions with Atg8-family members.…”
Section: Introductionmentioning
confidence: 99%
“…SRXN1 is a redox‐activated thiol switch important in the reversal of glutathionylation reactions (Findlay et al., 2006), while AKR1B1 is involved in lipid peroxidation detoxification (Barski, Tipparaju, & Bhatnagar, 2008). SQSTM1 and PICALM have both been implicated in autophagy (Moreau et al., 2014; Pankiv et al., 2007). However, given the small differences between the organic copper compounds and CuSO 4 and the very variable response with the inorganic copper product, these may not be suitable markers to monitor organic copper overload.…”
Section: Discussionmentioning
confidence: 99%